Electroglottography in the diagnosis of laryngeal disorders - Sunil .B. Bhoj, N.P. Nataraja, A. Jagadish (Journal of All India Institute of Speech and Hearing, 1970)
Clinicians have relied on two basic techniques in the assessment of Laryngeal Pathology, listening to the voice and viewing the larynx with a mirror or other device.  While much can be learned by the perceptual evaluation of voice quality, these judgements often are unreliable in a clinical setting.